The Effect of Myofascial Release on Pain Levels in the Condition of Myofascial Pain Syndrome in the Upper Trapezius Muscle in Students of Stikes Kesdam IV/Diponegoro Semarang - Syurrahmi Syurrahmi; Purna Luberto; Cintya Putri Anisah; Aisya Rahmah (International Journal of Medicine and Health, 2023)
Working position when typing is closely related to ergonomics or comfort issues, especially in the areas of design, position and proper body posture. MTrPs is a condition describing acute or chronic soft tissue pain, which occurs in muscles or muscle fascia. MTrPs cause contraction of knots or nodes that can form in a muscle band junction which is a source of pain. Pain or discomfort in the form of a prickling, throbbing, cutting and burning sensation in the loose connective tissue that covers the trapezius muscle due to trigger points. Data on computer workers in the Pedurungan Wetan area is 24 workers. This research method is a pre-experimental one group pre and post test design and sampling using purposive sampling technique. The population of this research is rental workers who work in Tlogosari Wetan, Pedurungan, Semarang City. The research instrument uses VAS (Vasual Analog Skill). The research stages consist of preparation, implementation and processing of research data. The steps taken at the preparation stage are literature study, field survey, outreach to rental workers. The implementation stage is carried out by collecting data. The results of this study showed that there was a relationship between typing time and the occurrence of MTrPs in the Upper Trapezius Muscle.